Mechanical flexibility, photosalience, and acidochromism of benzylidene indanone-based molecular crystals - Ahamed, Riyaaz; Bhowmik, Aritra; Mishra, Manish Kumar; Ghosh, Soumyajit (Crystal Growth & Design, 2025)
Molecular crystals that respond to multiple external stimuli are of great interest in smart, responsive materials in various fields. However, the integration of multiple responsive properties within the same crystal still remains a significant challenge for materials scientists due to the complex structural and electronic interactions. Previous studies on benzylidene indanone-based molecular crystals have shown only mechanical plasticity; however, we design crystals to elicit diverse responses to external stimuli, including mechanical stress, light, and acid vapor. Herein, we report two benzylidene indanone derivative-based crystals 1 and 2. Crystal 1 is mechanically brittle and exhibits light-induced photosalient splitting and jumping, attributed to [2 + 2] cycloaddition facilitated by the presence of a vinyl moiety. On the other hand, crystal 2 demonstrates anisotropic mechanical flexibility, exhibiting elasticity on one face and plasticity on alternate faces. Furthermore, crystals 1 and 2 both display reversible acidochromism in response to acid vapor. A detailed structure-property correlation has been established to elucidate the distinct mechanical responses of these molecular crystals. The development of such multistimuli-responsive smart materials holds significant potential for applications in flexible acid sensors, multifunctional responsive smart devices, and actuators, paving the way for advanced smart or intelligent molecular materials with tunable mechanical and optical properties.